2011
DOI: 10.1242/dev.046870
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cofilin phosphorylation and asymmetry in collective cell migration during morphogenesis

Abstract: SUMMARYDuring Drosophila oogenesis, two actin dynamics regulators, cofilin and Rac, are required for the collective migration of a coherent cluster of cells called border cells. Cell culture data have shown that Rac and cofilin are both essential for lamellipodium formation, but Rac signaling results in phosphorylation and hence inactivation of cofilin. So it remains unclear whether cofilin phosphorylation plays a promoting or inhibitory role during cell migration. We show here that cofilin is required for F-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 32 publications
3
62
0
Order By: Relevance
“…Because Ssh directly activates Cofilin through dephosphorylation, we first examined whether increased phospho-Cofilin (P-Cofilin) signal was detectable in the axons of the ssh 1-63 clone. We used a P-Cofilin antibody (Zhang et al, 2011) and detected a broad increase in the P-Cofilin signal (Fig. 5A″, red outline) in the ssh 1-63 mutant axons compared with the internal control axons (Fig.…”
Section: N17mentioning
confidence: 99%
“…Because Ssh directly activates Cofilin through dephosphorylation, we first examined whether increased phospho-Cofilin (P-Cofilin) signal was detectable in the axons of the ssh 1-63 clone. We used a P-Cofilin antibody (Zhang et al, 2011) and detected a broad increase in the P-Cofilin signal (Fig. 5A″, red outline) in the ssh 1-63 mutant axons compared with the internal control axons (Fig.…”
Section: N17mentioning
confidence: 99%
“…Twinstar encodes the only Drosophila homolog of Cofilin (Chen et al, 2001), an actin-binding protein, actindepolymerizing activity of which is inhibited through phosphorylation by LIM-kinase, which, in turn, is regulated by ROCK/Rok (Maekawa et al, 1999). Mutations in tsr have been shown to affect border cell migration and planar cell polarity in Drosophila (Blair et al, 2006;Zhang et al, 2011 ) that was shown previously to have no effect on salivary gland development on its own (Chandrasekaran and Beckendorf, 2005). Loss of tsr function in Rho1 1B homozygous embryos significantly suppressed the cell rearrangement and apical domain elongation defects of Rho1 1B mutant glands, which, in turn, narrowed the expanded lumens (Fig.…”
Section: Rho1mentioning
confidence: 99%
“…Our previous studies showed that cofilin is genetically required for cell migration in the Drosophila ovary and that it promotes lamellipodial protrusions (Chen et al, 2001;Zhang et al, 2011). Other genetic studies have shown that cofilin is essential for a variety of cellular and developmental processes requiring strong actin dynamics, including cytokinesis, axon growth and endocytosis (Bamburg, 1999;Ono, 2003).…”
Section: Introductionmentioning
confidence: 99%